Citrix XenApp 6.5 expert cookbook : over 125 recipes that enable you to configure, administer, and troubleshoot a XenApp infrastructure for effective application virtualization /: over 125 recipes that enable you to configure, administer, and troubleshoot a XenApp infrastructure for effective application virtualization. (2014) - Unknown
No abstract available